Effect of visual stimuli of pain on empathy brain network in people with and without Autism Spectrum Disorder. (23rd September 2018) - Lassalle, Amandine; Zürcher, Nicole R.; Hippolyte, Loyse; Billstedt, Eva; Porro, Carlo A.; Benuzzi, Francesca; Solomon, Patricia; Prkachin, Kenneth M.; Lemonnier, Eric; Gillberg, Christopher; Åsberg Johnels, Jakob; Hadjikhani, Nouchine
Abstract: The extent to which affective empathy is impaired in Autism Spectrum Disorder (ASD) remains unclear, as some—but not all—previous neuroimaging studies investigating empathy for pain in ASD have shown similar activation levels to those of neurotypicals individuals. These inconsistent results could be due to the use of different empathy‐eliciting stimuli. While some studies used pictures of faces exhibiting a painful expression, others used pictures of limbs in painful situations. In this study, we used fMRI to compare activation in areas associated with empathy processing (empathy network) for these two types of stimuli in 31 participants (16 with ASD, 15 controls). We found a group difference in the inferior frontal gyrus (IFG) and the thalamus when participants viewed stimuli of limbs in painful situations, but not when they viewed face stimuli with a painful expression. Both groups of participants activated their empathy network more when viewing pictures of limbs in painful situations than when viewing pictures of faces with a painful expression; this increased activation for limbs versus faces was significantly enhanced in controls relative to ASD participants, especially in the secondary somatosensory cortex (SII). Our findings suggest that empathy defect of people with ASD is contingent upon the type of stimuli used, and may be related to the level of Mirror Neuron System involvement, as brain regions showing group differences (IFG, SII) underlie embodiment. We discuss the potential clinical implications of our findings in terms of developing interventions boosting the empathetic abilities of people with ASD. Abstract : Individuals with autism have intact affective empathy when they see faces of people suffering, but show reduced brain activation in regions underlying embodiment compared with controls when they see limbs in painful situations. Autism is therefore not a disorder of reduced affective empathy, but is associated with difficulties in embodying stimuli that do not directly reflect the perception of pain by others.